Perkuliahan Online: Bagaimana Literasi Digital Calon Guru Matematika Berbantuan Lembar Kerja Etnomatematika dan GeoGebra? - Eka Sulistyawati; Dwi Shinta Rahayu (Jurnal Inovasi Matematika, 2022)
To support learning process during Covid-19 pandemic, digital literacy skills which is 21st century skill, is an important skill in learning. This research aimed to describe digital literacy skills of prospective mathematics teacher during the covid-19 pandemic. A qualitative descriptive was designed with 32 prospective mathematics teacher at IAIN Kediri. Student worksheets based on Ethnomathematics assisted by GeoGebra was used as a tool for implementing digital literacy skills in geometry courses during Covid-19 pandemic. Ethnomathematics worksheet was filled by student assessed using analitic rubric then described based on 3 digital competency indicators by Calvani namely technology, cognitive and ethnics. The results show that on technological indicator students can use GeoGebra tools to combine basic geometric and several polygons to produce other meaningful shapes, used GeoGebra tools to form regular polygons, able to make geometric fractals by applying geometric transformations, and created new tools for creating geometric fractals. On cognitive indicators, students can determine the basic patterns and transformations used in fractals and determine the types of fractals and non-fractals by using various sources. On ethical indicators students can present and interact directlywith lecturer and other students through GeoGebra classrooms.